Label-free visualization of cellular response to molecularly targeted agents using multiplex coherent anti-Stokes Raman scattering and third harmonic generation microscopy. (1st October 2022) - Oka, Yuki; Shen, Larina Tzu-Wei; Mori, Tomoko; Iwamura, Takumi; Leproux, Philippe; Matsusaka, Satoshi; Kano, Hideaki
Abstract: Cellular responses to molecularly targeted agents (gefitinib and osimertinib) have been observed in cultured cancer cells using ultra-broadband multiplex coherent anti-Stokes Raman scattering and third harmonic generation microscopy. Lipid droplets (LDs) appeared in the cells 48 h after the exposure of cancer cells to gefitinib. This was also observed in the gefitinib-resistant strain, and the accumulation of LDs was significant. When exposed to osimertinib, LDs were not as pronounced as those with gefitinib. These agents act on cells through different mechanisms.